PENGARUH PENGGUNAAN JENIS MEDIA TANAM DAN KONSENTRASI AB MIX TERHADAP PERTUMBUHAN MICROGREEN BROKOLI (Brassica olereceae L.) - Keese - Ngabwe; Dewi Firnia; Susiyanti - Susiyanti (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2025)
Microgreens are young vegetable seedlings harvested at an early growth stage after germination, known for their high nutritional content and bioactive compounds. The study examined how various types of media and AB-Mix nutrient levels affect the growth of broccoli microgreens. The experiment was arranged in a two-factor Completely Randomized Design (CRD) with four types of growing media (water, sand, cocopeat, and burnt rice husk) and four AB-Mix nutrient concentrations (0 ppm, 300 ppm, 600 ppm, and 900 ppm), each treatment replicated three times. Observed parameters included plant height, stem diameter, root length, leaf number, and germination percentage, measured at the first and second weeks after sowing. The results showed that both individual factors and their interaction had a significant effect on all growth parameters (p < 0.01). The combination of cocopeat and 600 ppm AB-Mix yielded the most optimal growth across all variables. Higher concentrations above 600 ppm tended to reduce plant performance, presumably due to osmotic stress. Cocopeat’s favorable physical properties supported water availability, aeration, and nutrient retention. In conclusion, the combination of cocopeat and 600 ppm AB-Mix is recommended as an optimal, efficient, and practical cultivation strategy for broccoli microgreens, particularly in sustainable urban farming systems.